find if x=3 is a root of equation kx square -10x+3=0
Answers
Answered by
9
↑ Here is your answer ↓ _____________________________________________________________ _____________________________________________________________
![kx^2 -10x + 3 = 0 kx^2 -10x + 3 = 0](https://tex.z-dn.net/?f=kx%5E2+-10x+%2B+3+%3D+0)
![x=3 x=3](https://tex.z-dn.net/?f=x%3D3)
![k(3)^2 - 10(3) + 3 = 0 k(3)^2 - 10(3) + 3 = 0](https://tex.z-dn.net/?f=k%283%29%5E2+-+10%283%29+%2B+3+%3D+0)
![9k - 30 + 3 =0 9k - 30 + 3 =0](https://tex.z-dn.net/?f=9k+-+30+%2B+3++%3D0)
![9k - 27 = 0 9k - 27 = 0](https://tex.z-dn.net/?f=9k+-+27+%3D+0)
![9k = 27 9k = 27](https://tex.z-dn.net/?f=9k+%3D+27)
![k = 27/9 k = 27/9](https://tex.z-dn.net/?f=k+%3D+27%2F9)
![k=3 k=3](https://tex.z-dn.net/?f=k%3D3)
Answered by
6
Find :- k
==============
Given that x =3
____________________
Putting the value of x,
=> Kx² -10x + 3 =0
=> K(3)² -10(3) + 3 = 0
=> K(9) - 30 + 3 = 0
=> 9k - 27 = 0
=> 9k= 27
=> K = 27/9
=> k = 3
I hope this will help you
-by ABHAY
==============
Given that x =3
____________________
Putting the value of x,
=> Kx² -10x + 3 =0
=> K(3)² -10(3) + 3 = 0
=> K(9) - 30 + 3 = 0
=> 9k - 27 = 0
=> 9k= 27
=> K = 27/9
=> k = 3
I hope this will help you
-by ABHAY
abhi569:
(-:
Similar questions